Do (P)Mdb À Anc A Oposição Legal E A Constituição De 1988 - Cruz, Sandra Maria Batista Da [UNIFESP] (2017)
This work seeks to empirically test the current version that the content of the provisions of the 1988 Federal Constitution resulted fundamentally from what can be called the Democratic Project of the (P)MDB, as it has been constituted and has been published in its Partisan Programs since 1971 (when the "Charter of Recife" explicitly called for the convening of a Constituent Assembly) until 1982, when the party released the document "Hope and Change", in which it clearly presents a systematic and detailed Government Program, predicting its transition from Opposition Legal to become effective alternative political power in the country. To do this, we have recovered the main elements of the long and troubled institutional trajectory of the Legal Opposition, from its institution by the new holders of power until its overwhelming victory in the 1986 elections, conquering most of the state governments and the 1987-88 ANC bench. In view of the limitations inherent to a Master's work, the empirical test we undertake is restricted to the Economic Order and Social Order, subfields we consider the mainstream of (P)MDB partidary program.